MEMBENTUK KARAKTER WIRAUSAHAWAN YANG KREATIF DAN TANGGUH - Suryaningtyas, Dyah (Universitas Slamet Riyadi, 2004)
ABSTRACT Entrepreneur are people who have the ability to see and value business opportunity, collect resources which are needed and take an action to gain the success. Basic attitude needed is eagerness and doing to take the risk. Thinking positively of himself is other attitude which can support him although he may fail. The fact show that the attitudes of Indonesian society is still low. To be a successful entrepreneur need those attitudes. Keywords: character, entrepreneur, creative, strong